Sigma Metrics Assessment as Quality Improvement Methodology in a Clinical Chemistry Laboratory - Monika Garg; Neera Sharma; Saswati Das (Indian Journal of Medical Biochemistry)
Background: The concept of sigma metrics and lean six sigma is well known in the field of health care. However, not many labs utilize the six-sigma metrics for the maintenance of high-quality laboratory performance. A minimum value of 3 σ is desired in any clinical laboratory and a value of σ ≥6 is regarded as the gold standard for obtaining high-quality lab reports. Objective: To calculate bias, Coefficient of variation (CV) and sigma metrics from the internal quality control (IQC) and external quality control (EQC) data to ascertain the extent of quality management. Materials and methods: An extensive study of sample processing and quality practices was carried out in the Central Laboratory of Department of Biochemistry, PGIMER and Dr. RML Hospital, New Delhi; from February 2020 to July 2020. The IQC used (both Level I and II) was from Biorad Laboratories India (Lyphochek assayed chemistry control) and the EQC used was from Randox Laboratories, UK. All the controls were run on Beckman Coulter clinical chemistry analyzer AU 680. A total of 14 clinical parameters were analyzed and subsequently, mean SD, CV, bias and σ were calculated through their respective formulas. Results: Amylase showed σ >6 for both levels of IQC. It indicates world-class performance. Total bilirubin, AST, triglyceride and HDL depicted σ values between 3.1 and 6 for both L1 and L2. Iron showed an σ value of 5.5 in L1 whereas it was 3.78 in L2. The remaining parameters had σ <3 in L1. As far as L2 is concerned, besides ALT which had σ value of 4.24; the rest of all analytes had σ <3. Conclusion: Sigma metrics in the clinical laboratory are an essential technique to ascertain poor assay performance, along with the assessment of the efficiency of the existing laboratory process.